Drosophila crinkled, mutations of which disrupt morphogenesis and cause lethality, encodes fly myosin VIIA. - Kiehart, D.P.; Franke, J.D.; Chee, M.K.; Montague, R.A.; Chen, T.L.; Roote, J.; Ashburner, M. (Genetics, 2004)
Myosin VIIs provide motor function for a wide range of eukaryotic processes. We demonstrate that mutations in crinkled (ck) disrupt the Drosophila myosin VIIA heavy chain. The ck/myoVIIA protein is present at a low level throughout fly development and at the same level in heads, thoraxes, and abdomens. Severe ck alleles, likely to be molecular nulls, die as embryos or larvae, but all allelic combinations tested thus far yield a small fraction of adult "escapers" that are weak and infertile. Scanning electron microscopy shows that escapers have defects in bristles and hairs, indicating that this motor protein plays a role in the structure of the actin cytoskeleton. We generate a homology model for the structure of the ck/myosin VIIA head that indicates myosin VIIAs, like myosin IIs, have a spectrin-like, SH3 subdomain fronting their N terminus. In addition, we establish that the two myosin VIIA FERM repeats share high sequence similarity with only the first two subdomains of the three-lobed structure that is typical of canonical FERM domains. Nevertheless, the approximately 100 and approximately 75 amino acids that follow the first two lobes of the first and second FERM domains are highly conserved among myosin VIIs, suggesting that they compose a conserved myosin tail homology 7 (MyTH7) domain that may be an integral part of the FERM domain or may function independently of it. Together, our data suggest a key role for ck/myoVIIA in the formation of cellular projections and other actin-based functions required for viability.